Improvement of muscle quality in tilapia (Oreochromis niloticus) with dietary faba bean (Vicia faba L.) - Li, Qingqing; Huang, Yao; Zhang, Xingqian; Zou, Cuiyun; Lin, Li (Frontiers in Nutrition, 2023)
Tilapia (Oreochromis niloticus) is a freshwater fish which is farmed worldwide. Improving the muscle quality of fish has become a major goal while maintaining a sustainable aquaculture system. This research attempts to assess the effect of 0% (FB0), 40%(FB40), 50%(FB50), 60%(FB60) and 70% (FB70) faba bean on the texture parameter, histological analysis, proximate, amino acids, and fatty acids composition in tilapia fed 90 days. The results showed that hardness, chewiness, and shear force of tilapia muscle fed FB60, and FB70 were considerably more in comparison to fish fed FB0 at 90 days (P < 0.05). Tilapia fed faba beans had higher muscle fiber density, wider spaces between muscle fibers and smaller fiber diameter, with the greatest difference in tilapia fed FB60. The total protein content in tilapia fed FB40 was considerably more in comparison to in fish fed FB70 (P < 0.05), where the total protein content in muscle first increased and then reduced with increasing dietary faba bean level. The muscle ∑TAA, ∑EAA, valine, tyrosine, cysteine, aspartic acid, methionine, isoleucine, glutamic acid, leucine, arginine, and serine, contents in tilapia fed FB60 were much more in contrast to in fish fed FB0 (P < 0.05), which initially increased and then reduced with increasing dietary faba bean level. The muscle ∑PUFA content in tilapia fed dietary faba beans was greater compared with fish fed FB0, whereas the ∑SFA contents in tilapia fed FB50 and FB60 were lower in contrast to in fish fed FB0. In summary, dietary faba beans can improve muscle texture, muscle fibers, amino acids content and fatty acids content in tilapia. The research’s results make a contribution to the improved knowledge of the association among muscle quality in tilapia and dietary faba beans.